Increased Risk of Vitamin D Deficiency Among HIV-Infected Individuals: A Systematic Review and Meta-Analysis - Wang, Yingying; Huang, Xiaojie; Wu, Yaxin; Li, Aixin; Tian, Yakun; Ren, Meixin; Li, Zhen; Zhang, Tong; Wu, Hao; Wang, Wen (Frontiers in Nutrition, 2021)
Background: Human immunodeficiency virus (HIV) infection is a heavy burden worldwide. Observational studies have reported a high prevalence of vitamin D deficiency (VDD) among people living with HIV (PLWH). However, its deficiency is also a global health problem. Therefore, we conducted a meta-analysis and systemic review to compare differences between HIV-infected subjects and non-HIV-infected subjects. Methods: We searched PubMed, Web of Science, Embase, and Cochrane library. We extracted data, including demographic information, study type, vitamin D-related values, and HIV-related values, ultimately including 15 studies after removing duplicates and screening titles, abstracts, and full texts and finally performing a meta-analysis in terms of vitamin D level and vitamin D deficiency prevalence. Results: Regarding VDD prevalence, the HIV vs. the non-HIV group had an odds ratio of 1.502 (95% CI, 1.023–2.205; P = 0.038). In the subgroup analysis, the odds ratios were 1.647 (95% CI, 1.020–2.659; P = 0.041; I2 = 94.568) from 7 studies (age over 40), 2.120 (95% CI, 1.122–4.008; P = 0.021; I2 = 0.000) from 2 studies (BMI less than or equal to 25), 1.805 (95% CI, 1.373–2.372; P = 0.042; I2 = 74.576) from 7 studies (latitude <40), 2.120 (95% CI, 1.122–4.088; P = 0.021; I2 = 0.000) from 2 studies (only included male participants), and 2.296 (95% CI, 1.287–4.097; P = 0.005; I2 = 19.927) from 3 studies (only included ART-experienced participants). Thirteen studies were deemed to have moderate quality, while two had high quality. Conclusions: HIV infected subjects are prone to have VDD compared with general population. ART, older age, lower BMI, lower latitude and male sex may present risk factors for VDD in PLWH. Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=228096.